Statistical Literacy Ability Viewed from the Student's Field of Expertise and Curiosity - Setiani, Nurokhmi Wahyu; Dewi, Nuriana Rachmani; Rochmad, Rochmad (AlphaMath : Journal of Mathematics Education, 2021)
This study aims to describe statistical literacy skills based on the field of expertise and curiosity of grade XII student of SMK Komputama Jeruklegi. The type of research used is qualitative descriptive research. Sampling was done by purposive sampling technique. The study took four subjects from each category in each field of expertise in SMK Komputama Jeruklegi. Data collection using questionnaires, statistical literacy tests, and interview guidelines. The validation test used is a technical triangulation test. The results showed that of the two fields of expertise taken, students achieved two to four indicators of statistical literacy. For students of information and communication technology with curiosity is very high can meet all indicators of statistical literacy ability. Students with high curiosity meet indicators understand the data, present the data and draw conclusions. Students with curiosity are meeting indicators understanding the data and drawing conclusions. While students with low curiosity meet the indicator presents the data and draws conclusions. Then the results of students in the fields of business expertise and management show that students with very high curiosity and high meet indicators of understanding data, presenting data, and drawing conclusions. Students with curiosity are meeting indicators understanding the data and presenting the data. Whereas students with low curiosity meet the indicators understand the data and draw conclusions. This research is expected to contribute to students' statistical literacy skills, so that they can provide an overview of future research.